Influence of corrosion on the experimental behaviour of R.C. ties. (1st November 2019) - Imperatore, Stefania; Rinaldi, Zila; Spagnuolo, Simone
Highlights: Corroded full-scale R.C. ties are tested. The local and global behaviours are discussed. The crack pattern and widths are analysed. Influence of corrosion on the bond behavior and transmission length is pointed out. A comparison with a simplified approach of literature is presented. Abstract: Existing reinforced concrete elements are typically subjected to ageing and corrosion, leading to significant structural capacity decay. The variation in the steel-to-concrete interaction is one the first effects of corrosion, that consequently modify the bond-slip relationship. On a structural point of view, this implies a variation of the crack pattern, an increase of the element deformability, and an enlargement of the crack width. Several studies, available in the technical literature, analyse the corrosion influence on the bond properties by means of small specimens, in which only the local bond-slip behaviour can develop. In this paper, in order to investigate the problem at a full-scale level, three meters long tie rods were cast, artificially corroded and tested in the Laboratory of Materials and Structures of the University of Rome Tor Vergata. Each specimen was characterized by a 150 × 150 mm 2 cross-section and reinforced with a Ø16 steel bar placed at the centerline of the element. The specimens were artificially corroded up to about 4% corrosion level (in terms of mass loss) and subjected to tensile test. The obtained results clearly highlight the influence of the corrosion of the bond transmission mechanism.